The Community Health Worker Model: A Grass-Roots Approach for Measles Prevention in Refugee Camps - Baier, Kristina; Deonandan, Raywat (Université d'Ottawa | University of Ottawa, 2016)
Syria’s protracted civil war has resulted in massive population movements into refugee camps. Such movements, in conjunction with lower vaccination rates, potentiate infectious disease outbreaks. Measles transmission is a continuous threat in refugee camps, and a sustainable approach to providing preventative medicine in camps is warranted. The community health worker model can be used to identify unvaccinated persons, detect probable cases and refer individuals to health clinics within the camps for prophylaxis and medical care, respectively. Through this grass-roots approach, community health workers become an on-the-ground surveillance system that can determine demographic trends and facilitate public health responses to potential outbreaks.